Drug-Induced Peripheral Neuropathy: Diagnosis and Management - Merheb, Diala; Dib, Georgette; Zerdan, Maroun B.; Nakib, Clara El; Alame, Saada; Assi, Hazem I. (Current Cancer Drug Targets, 2022)
Peripheral neuropathy comes in all shapes and forms and is a disorder which is found in the peripheral nervous system. It can have an acute or chronic onset depending on the multitude of pathophysiologic mechanisms involving different parts of nerve fibers. A systematic approach is highly beneficial when it comes to cost-effective diagnosis. More than 30 causes of peripheral neuropathy exist ranging from systemic and auto-immune diseases, vitamin deficiencies, viral infections, diabetes, etc. One of the major causes of peripheral neuropathy is drug-induced disease, which can be split into peripheral neuropathy caused by chemotherapy or by other medications. This review deals with the latest causes of drug-induced peripheral neuropathy, the population involved, the findings on physical examination and various workups needed and how to manage each case.
Keywords: proteasome inhibitors